Multiobjective generation portfolio of hybrid energy generating station for mobile emergency power supplies - Zhou, Bin (2020)
This paper proposes a mixed generation portfolio model of hybrid energy generating station (HEGS) for standby emergency power supply (EPS). The HEGS functions as a mobile and transportable reserve power source for critical loads in case of electricity outages. In the proposed model, various renewable and non-renewable energy sources with different mobility, energy density, and power density characteristics are integrated to form a sufficient and reliable hybrid energy EPS system, and the uncertainties of demand load, wind speed, solar radiation intensity, as well as solar cell temperature are modeled as interval numbers to formulate the optimal sizing problem of HEGS under uncertainty into a deterministic combinatorial optimization model. Furthermore, the multiobjective generation portfolio model of EPS configuration is also designed to generate Pareto frontier between implementation cost reduction and mobility improvement. Four generic evaluation metrics are formulated to evaluate the resulting generation-mix schemes of HEGS with case study demonstrated the effectiveness and superiority of the proposed model.